Pelaksanaan Pembelajaran Komunikasi Non-verbal Bahasa Arab dengan Bahasa Tubuh sebagai Pemahaman Kinesik Lintas Budaya - Isma'il (PROGRESSA: Journal of Islamic Religious Instruction, 2018)
Arabic is a universal language, Learning Arabic cannot be separated from the social and environmental environment that surrounds it. Learning Arabic requires adaptation to the environment which is an integral part of educational institutions. Students are part of the learning process, after formal education is complete, then they again become one of the important elements in society. Non-verbal language is statement forms of personality or personality traits that are manifested in body movements. Arabic is also an interesting study, where Arabic is one of the dominant Semitic languages and still persists today. Based on the focus of the study, this study aims to describe: The Implementation of Learning Arabic non-verbal communication with Body Language as a cross-cultural kinesic understanding. This research is "Library Research". The research data used is secondary data. The data collection technique used by the authors in this study is documentation. Data processing is carried out by conducting study activities, verification and reduction, grouping and systematization, and interpretation or interpretation so that a phenomenon has social, academic, and scientific value. While data analysis in this study was carried out during and after data collection using descriptive-critical-comparative methods, and content analysis methods. From the results of the analysis it was concluded that: 1) In its development language became a feature of a culture. At a minimum it becomes a differentiator between one community and another in terms of language use. 2) Since the first year of his life in the world, children take part in conversations using body language and non-verbal cues. Then little by little they learn linguistic codes of language, how codes represent objects, events and types of relationships between objects and events. They learn how to send and receive orders with spoken language. 3) The role of Arabic in national culture has taken an important part since the development of Islam in the archipelago in the XIII century and its role is still felt lexically and semantically.